Perceptions, Career Motivation on Interest in Following Professional Education Accounting Case Studies in Students: Persepsi, Motivasi Karir Terhadap Minat Mengikuti Pendidikan Profesi Akuntansi Studi Kasus Pada Mahasiswa - Ronni Andri Wijaya (International Journal of Technology Vocational Education and Training, 2020)
This research has four main objectives. First, to determine the effect of perceptions on interest in taking accounting profession education. Second, to determine the effect of degree motivation on interest in taking accounting profession education. Third, to determine the effect of career on interest in taking accounting profession education. And fourth, to determine the effect of perceptions, degree motivation, and career on interest in participating in accounting professional education in Accounting Study Program students of UPI YPTK PADANG. This research is a quantitative research. The data collection technique used in this study was a survey. The population of this study were 706 active students majoring in accounting class 2017 and 2018 at Putra Indonesia University YPTK Padang. And the sample of this research is using the Slovin formula with a critical value of 0.05 in order to obtain 255. To answer the research hypothesis, the data were analyzed using multiple regression tests. The results showed that the variables of perception, degree motivation, career, had a positive and significant effect on students' interest in attending Accounting Professional Education (PPAk).